A Five-Year Trend of Intestinal Parasite Prevalence among Students Attending Clinic at University of Gondar, Northwest Ethiopia - Adane Derso; Gizachew Yenealem; Ayenew Addisu (Journal of Parasitology Research)
Background. Intestinal parasitic infections are the cause of the highest worldwide infectious disease and the major public health problems in developing countries. Among the cases, children and younger age are at high risk and the major victims. The aim of this study was to assess the five-year trend of intestinal parasite prevalence among University of Gondar students. Method. A retrospective cross-sectional study was conducted to assess the trend of intestinal parasite prevalence among students at the University of Gondar. The data was collected from students who have studied at the University of Gondar from 2014 to 2018 and who visited the student’s clinic and had recorded results of stool sample diagnosis on the laboratory logbook. Stool specimens were examined using direct saline wet mount methods. The data was analyzed by using SPSS version 20 software, and P value < 0.05 was considered as statistically significant. Moreover, chi-square was used to assess the association of different variables. Result. During the study period, a total of 6244 stool samples were requested for intestinal parasite diagnosis and it was found that 2850 specimens were positive for intestinal parasites, representing an overall prevalence of 45.6% with a fluctuating trend. Ten different parasites were reported with Entamoeba histolytica/dispar (20.3%) and Giardia lamblia (8.2%), the most frequently detected intestinal parasites. The prevalence of intestinal parasitic infections was higher in males (35.4%) than females (10.2%) (P=0.02). Conclusions. Intestinal parasitic infection was highly prevalent, and there were fluctuations in the prevalence of intestinal parasites from 2014 to 2018. Environmental sanitation improvement and health education schemes at the University of Gondar can be considered quite indispensable for the prevention and control of parasitic infections in the area.